The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/01.aog.0000250969.15438.17
|View full text |Cite
|
Sign up to set email alerts
|

Torsion of Normal Adnexa in Postmenarchal Women and Risk of Recurrence

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
3
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 15 publications
4
87
3
11
Order By: Relevance
“…Given the possible confusion of torsion in pregnancy with other conditions, it may be thought that the diagnosis of torsion in these cases would be delayed. However, the median time from admission to surgery in our cohort was 6 hours, which is shorter than the mean time from admission to surgery we found in a nonpregnant population in our previous study (7). Nevertheless, when analyzed separately for early and late pregnancy, we did find that patients in the second and third trimesters were operated significantly later that those in the first trimester.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Given the possible confusion of torsion in pregnancy with other conditions, it may be thought that the diagnosis of torsion in these cases would be delayed. However, the median time from admission to surgery in our cohort was 6 hours, which is shorter than the mean time from admission to surgery we found in a nonpregnant population in our previous study (7). Nevertheless, when analyzed separately for early and late pregnancy, we did find that patients in the second and third trimesters were operated significantly later that those in the first trimester.…”
Section: Discussioncontrasting
confidence: 86%
“…Again, the paucity of previous studies and the small number of cases in the current study does not enable us to establish a definite association. We have previously described torsion of normal adnexa in postmenarchal nonpregnant women (7). The causes of torsion in their case may be hypermobile ovarian ligaments, long ovarian ligaments, or other inherent ovarian mobility.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we were unable to identify a significant difference in the frequency of acute abdominal pain when compared between patients with and without ovarian torsion (P = 1.00). Although most laboratory findings are normal in patients with ovarian torsion, some studies have identified a minor degree of leukocytosis in 27%-50% of patients (12,13). In the present study, only 20% of the patients with ovarian torsion exhibited leukocytosis, and no statistical difference was found in the frequency of leukocytosis when compared between patients with and without ovarian torsion (P = 1.00).…”
Section: Discussioncontrasting
confidence: 78%
“…The incidence ranges between 22 and 50% [11][12][13] and usually occurs in the pediatric population. The purpose of this study was to evaluate the relationship between the length of the ovarian ligament and ovarian torsion.…”
Section: Introductionmentioning
confidence: 99%